Sistem Temu Kembali Informasi Pesawat Udara Militer Menggunakan Jaringan Syaraf Tiruan Back Propagation Network - Vira Bahrudin , Ardyansyah; Datumaya Wahyudi Sumari , Arwin; Afif Hendrawan , Muhammad (Jurnal Teknik Ilmu dan Aplikasi, 2023)
Various war events in various parts of the world between two or more countries along with various high-tech war equipment such as military aircraft arouse curiosity to find out more about these war equipment, getting this information is still hampered by the lack of existing information, a lot of information is available in printed form, in museums managed by the Indonesian National Army (TNI), and in the form of books about military aircraft. The design of a Military Aircraft Information Retrieval System Using Machine Learning is aimed at providing information to the public about types of military fighter aircraft, this is due to the lack of information about fighter aircraft in the military world among the public.